Non-interpenetrated metal-organic frameworks based on copper(II) paddlewheel and oligoparaxylene-isophthalate linkers: synthesis, structure and gas adsorption - Yan, Yong; Juricek, Michal; Coudert, Francois-Xavier; Vermeulan, Nicolaas A.; Grunder, Sergio; Dailly, Anne; Lewis, William; Blake, Alexander J.; Stoddart, J. Fraser; Schröder, Martin (American Chemical Society, 2016)
Two metal–organic framework materials, MFM-130 and MFM-131 (MFM = Manchester Framework Material), have been synthesized using two oligoparaxylene (OPX) tetracarboxylate linkers containing four and five aromatic rings, respectively. Both fof-type non-interpenetrated networks contain Kagomé lattice layers comprising [Cu2(COO)4] paddlewheel units and isophthalates, which are pillared by the OPX linkers. Desolvated MFM-130, MFM-130a, shows permanent porosity (BET surface area of 2173 m2/g, pore volume of 1.0 cm3/g), high H2 storage capacity at 77 K (5.3 wt% at 20 bar and 2.2 wt% at 1 bar), and a higher CH4 adsorption uptake (163 cm3(STP)/cm3 (35 bar and 298 K)) compared with its structural analogue, NOTT-103. MFM-130a also shows impressive selective adsorption of C2H2, C2H4, and C2H6 over CH4 at room temperature, indicating its potential for separation of C2 hydrocarbons from CH4. The single-crystal structure of MFM-131 confirms that the methyl substituents of the paraxylene units block the windows in the Kagomé lattice layer of the framework, effectively inhibiting network interpenetration in MFM-131. This situation is to be contrasted with that of the doubly interpenetrated oligophenylene analogue, NOTT-104. Calculation of the mechanical properties of these two MOFs confirms and explains the instability of MFM-131 upon desolvation in contrast to the behavior of MFM-130. The incorporation of paraxylene units, therefore, provides an efficient method for preventing network interpenetration as well as accessing new functional materials with modified and selective sorption properties for gas substrates.